A Stylistic Analysis of Two Selected, English and Arabic, War Poems (Journal of the College of Languages (JCL), 2015)
War as a human phenomenon, has its own literature. Poetry is a major genre in this literature. This paper is an attempt to investigate and analyse some stylistic features in two selected, English and Arabic, war poems. These poems share the same theme.Both promote the principle of sacrificing one’s own life for the sake of homeland. This paper limits itself to analyse, thecontent words, tenses, semantic grouping of vocabulary and foregrounding in the two poems. The areas of analysis show great similarities in distributing the general content words (nouns, verbs, adjectives, and adverbs). In the analysis of the semantic areas of each content word, these poems reveal some similarities and some differences in their frequency rates. The poets, in both poems, resort to the present tense to express their thoughts.Bothpoems demonstrate foregrounding, though in different degrees, in using repetition, deviation and parallelism.The sole significant difference is in the frequency use of adjectives, which is higher in the English poem than in the Arabic poem.